Influence of fiber hollowness on the local thermo-electro-elastic field in a thermoelectric composite - Yu, Chuanbin; Liu, Haoxin; Du, Chaofan; Xing, Shichao (Frontiers in Energy Research, 2023)
In this study, we consider the plane problem of a hollow fiber embedded within a nonlinear thermoelectric medium in the presence of uniform remote in-plane electric current and uniform remote energy flux. Closed-form expressions for all the potential functions characterizing the thermoelectric field and the associated thermal stress field in both the matrix and fiber are obtained by utilizing the complex variable method. Numerical examples are presented to illustrate the effect of hollowness ratio of the fiber on the local energy conversion efficiency and interfacial thermal stress concentration. It is found that a higher conversion efficiency and a lower amount of thermal stress concentration around a hollow fiber than that around a solid fiber could be achieved simultaneously by appropriate selection of the hollowness ratio of the fiber.